2018
DOI: 10.1016/j.adaj.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The pathway from cognitive impairment to caries in older adults

Abstract: As a result of cognitive impairment, impaired DRF plays a critical role in the pathway from cognitive impairment to oral health decline. Therefore, DRF assessment should be a standard component of geriatric dental assessment. A functionally-tailored oral hygiene intervention is essential to improve oral health for persons with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Evidence shows that oral self‐care function plays a critical role in oral health deterioration in PWCI . These findings suggest that oral self‐care and other DRF should be considered during clinical treatment planning.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Evidence shows that oral self‐care function plays a critical role in oral health deterioration in PWCI . These findings suggest that oral self‐care and other DRF should be considered during clinical treatment planning.…”
Section: Discussionmentioning
confidence: 91%
“…32 Evidence shows that oral self-care function plays a critical role in oral health deterioration in PWCI. 12,40,41,50 Second, it was a secondary analysis using the data of a cross-sectional study, and the design limits us from determining the temporal relationship between cognition impairment, DRF decline and oral health. Therefore, the causal relationships between cognitive, functional and oral health measures remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that patients with cognitive impairment generally find it difficult to maintain good oral hygiene and are more susceptible to oral diseases . Many individuals with cognitive impairment experience oral diseases such as dental caries and periodontal diseases, which lead to tooth loss . Conversely, oral health can also affect cognitive functioning in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with cognitive impairment experience difficulties in managing their ADL, which may be a factor that complicates oral health management . In a population‐based study on elderly participants that analysed ADL and cognitive function using Cox proportional hazards regression models controlled for other covariates such as age and sex, it was concluded that ADL disability was a strong risk factor for dementia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation